Assessment of tuberculosis spatial hotspot areas among smear positive pulmonary tuberculosis patients attending JSS: a tertiary health care centre from Mysore district, South India - Manthravadi, Krishna Karthik; Anantharaj, Tejashree; Badveti, Satya Sai (International Journal Of Community Medicine And Public Health, 2019)
Background: Tuberculosis (TB) is a disease of public health concern, with a varying distribution across settings depending on socio-economic status, HIV burden, availability and performance of the health system. In 2017, TB caused an estimated 1.3 million deaths (range, 1.2–1.4 million) among HIV-negative people, and there were an additional 300 000 deaths from TB (range, 266 000–335 000) among HIV-positive people. The current TB program reports are often compiled and reported at higher administrative units and there is limited information about the spatial distribution of the disease. Hence, we aimed to assess the spatial distribution and hot spot areas of the disease among the patients attending a tertiary care centre in Mysore over a period of 3 years. Methods: This is a taluk based study, the spatial analysis and hot spot area identification was done by collecting the demographic data from the smear positive pulmonary tuberculosis patients attending JSS a tertiary care centre from Mysore district. Hot spot areas and areas with TB transmission are identified and estimated using GIS software tool. Distribution of TB incidence was mapped with the population density from 2016-2018. Results: Spatial mapping of smear positive tuberculosis revealed that majority of cases were recorded from Mysore city followed by T. N. Pura and Hunsur taluk regions. Conclusions: This study emphasized on finding hot spot areas and local clusters involved in TB transmission.